The Effect of Emotionally-Focused Couples Therapy on Sexual Self-Schemas, Sexual Self-Concept, and Sexual Dysfunction in Infertile Women with Polycystic Ovary Syndrome - Marashian, Fatemeh Sadat (Advances in Nursing & Midwifery, 2023)
Abstract Introduction: Physical and appearance changes and the imbalance of sex hormones can decrease the quality of life and sexual performance of infertile women with polycystic ovary syndrome (PCOS). Therefore, this study investigated the effectiveness of emotionally focused couple’s therapy on sexual self-schemas, sexual self-concept, and sexual dysfunction in infertile women with PCOS. Methods: This was a quasi-experimental study with a pretest-posttest and a control group. The statistical population included all infertile women with PCOS referred to the Ahvaz Health Center in 2022. Thirty women were selected using convenience sampling and randomly divided into two groups: experimental and control (n=15 per group). The experimental group participated in eight sessions of emotionally focused couple’s therapy, but the control group did not receive any intervention. The sexual self-schemas, sexual self-concept, and sexual dysfunctional beliefs questionnaires were employed to collect data. We used Descriptive statistics and analysis of covariance (ANCOVA) to analyze the data. Results: The mean ±SD of the posttest score of sexual self-schemas, sexual self-concept, and sexual dysfunction in the experimental group was 29.23 ± 5.14, 28.77 ± 461, and 35.96 ± 1.37, respectively. Moreover, the mean ±SD of the posttest score of sexual self-schemas, sexual self-concept, and sexual dysfunction in the control group was 36.66 ± 4.57, 22.29 ± 2.13, and 41.00 ± 2.89, respectively. The results showed that in the post-test stage, there was a considerable difference between the mean scores of sexual self-schemas, sexual self-concept, and sexual dysfunction in the experimental and control groups (P < 0.001). Conclusions: Emotionally focused couples therapy improved sexual self-schemas, sexual self-concept, and sexual dysfunction in women with PCOS. The researchers suggested using emotionally focused couples therapy as a complementary treatment in medical centers to improve the sexual performance of infertile women with PCOS.